2015
DOI: 10.1021/acs.joc.5b01592
|View full text |Cite
|
Sign up to set email alerts
|

Construction of All-Carbon Quaternary Centers through Cu-Catalyzed Sequential Carbene Migratory Insertion and Nucleophilic Substitution/Michael Addition

Abstract: A Cu-catalyzed three-component cross-coupling reaction of terminal alkyne, α-diazo ester, and alkyl halide has been developed. This transformation involves sequent migratory insertion of copper-carbene and nucleophilic substitution, in which a C(sp)-C(sp(3)) bond and a C(sp(3))-C(sp(3)) bond are formed successively on a carbenic center. Michael addition acceptors can also be employed instead of alkyl halides that enable Michael addition to be an alternative way to build C(sp(3))-C(sp(3)) bond. This transformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…of TEMPO is needed in this hemicycle, as expected and demonstrated in the optimization of the conditions. After the intersection of the two cycles, the most notable point is the Wagner–Meerwein 1,2‐shift of the phenyl group to form an on‐ring α‐diarylated all‐carbon quaternary center, which is otherwise inaccessible …”
Section: Resultsmentioning
confidence: 99%
“…of TEMPO is needed in this hemicycle, as expected and demonstrated in the optimization of the conditions. After the intersection of the two cycles, the most notable point is the Wagner–Meerwein 1,2‐shift of the phenyl group to form an on‐ring α‐diarylated all‐carbon quaternary center, which is otherwise inaccessible …”
Section: Resultsmentioning
confidence: 99%
“…In this case the carbene source is an α-diazo ester that reacts first with the alkyne to form the C(sp)-C(sp 3 ) bond and then with either an alkyl halide or a Michael acceptor to construct the C(sp 3 )-C(sp 3 ) bond furnishing an all-carbon quaternary centre (Scheme 23, b). 29 The same group reported another three-component reaction in which the allenyl copper intermediate, and not the propargyl copper one, formed after the first coupling reaction was trapped with an electrophile (Scheme 23, c). 30 N-tosylhydrazones derived from both aldehydes and ketones were competent substrates.…”
Section: Scheme 22mentioning
confidence: 99%
“…Later, it was shown that various α-diazo-γ-butyrolactones can be synthesized in direct diazo transfer conditions at low temperatures. However, this method did not gain popularity because of the formation of large numbers of triazine and azide side-products [ 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 ]. Much better results were achieved using detrifluoroacetylating diazo transfer, which to-date is the most widely accepted method of synthesizing α-diazo lactones, including six- and seven-membered ones ( Scheme 73 ) [ 5 , 96 , 109 , 110 ].…”
Section: α-Diazo Lactonesmentioning
confidence: 99%
“…α-Diazo-γ-butyrolactones can also be obtained from α-acetyl γ-butyrolactones. In this case, the diazo transfer reaction is usually conducted using trifluoromethane sulfazide generated in situ under phase transfer conditions [ 111 , 112 , 113 ]. In addition, later it was shown that the practical protocol of SAFE diazo transfer (vide supra) is also applicable for deacetylative diazo transfer with good yield ( Scheme 74 ) [ 114 ].…”
Section: α-Diazo Lactonesmentioning
confidence: 99%
See 1 more Smart Citation